Comportamento de sementes de cultivares de soja,submetidos a diferentes períodos de envelhecimentoacelerado - da Silva, Josué Bispo; Lazarini, Edson [UNESP]; de Sá, Marco Eustáquio [UNESP] (My University, 2010)
Accelerated aging test is an important procedure to be used, beyond other aim, for breeding rograms to select cultivars with storage and development potential under high relative humidity and temperature. At accelerated aging test in soybean seeds, the temperature and time of exhibition they were not still totally established, factors that cause divergence among the researchers, mainly with relationship to the most appropriate periods. The aim was to evaluate the behavior of soybean seeds submitted to accelerated aging test. Seeds of the varieties IAC-15, CAC-1, FT-Estrela and IAC-Foscarin 31 were submitted to germination test, electrical conductivity and accelerated aging (41°C, during 44, 48, 52, 56, 60, 64, 68, 72 and 76 hours). There are differences among cultivars evaluated in relation to accelerated aging test sensibilility; the cultivars are sensibles to increasing the exposition time; the accelerated aging test can be used to select cultivars in breeding programs; the cultivar FT-Estrela can be sowed at regions with high temperature and humidity.
Behavior of soybean seeds cultivars under different times on the accelerated aging test
Keywords: Glycine max physiological seed quality; Vigor tests